Petrological and Magnetic Fabric in the South Region of the Killarney Igneous Complex - Fair, Anastasia (My University, 1996)
Forty-Three cores were collected from the region of the Killarney Igneous Complex, southeast of the town Killarney. These cores were analysed by measuring geophysical properties such as bulk susceptibility, percent anisotropy, magnetic foliation and lineation and remanence. The magnetic fabric measured indicated a regional fabric. In some areas the fabric was completely overprinted due to localised deformation. Measured remanence may make it possible to determine the effect of previous deformations; however, none was seen in this study.
The petrological fabric was also investigated by taking thin sections perpendicular to the long axis of the core. Again it was possible to see a regional and localized deformation pattern due to reduced grain size, grain alignment and recrystallization.
Measurements collected from the samples determined that both the magnetic fabric and petrological fabric showed indications of being near areas of greater deformational intensities. A relationship was then established between the magnetic fabric and petrological fabric on a fine scale. This relationship may aid in determining direction and extent of deformation in the rock bodies when it is not easily identifiable in the field.
Keywords: Petrological; Magnetic Fabric; Killarney; Igneous Complex